2021
DOI: 10.3390/ijerph18115965
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Prevalence of and Factors Related to Non-Suicidal Self-Injury among Middle and High School Students in South Korea

Abstract: This study was conducted to estimate the prevalence of non-suicidal self-injury (NSSI)—the most severe mental health problem among South Korean adolescents in 2019. The participants were students from 12 middle and seven high schools in a single city in the metropolitan area in South Korea. A cluster-random sampling method was used—one class per school year at each middle and high schools. Every student in the selected classes was investigated. The final number of selected classes and students were as follows:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…This study examined the association of many factors with NSSI, found that students attending vocational high schools had a significantly higher prevalence of NSSI than middle school students as well as general high schools, and that school category was also an independent risk factor for NSSI in the regression equation, which may be due to the lower self-efficacy and lower self-esteem of vocational high school students compared to their counterparts in general middle and high schools (40). The prevalence of NSSI by gender was statistically significant and also an independent risk factor for NSSI, which is also consistent with most previous studies (19)(20)(21)(22). The difference in NSSI detection rates between those left-behind children and those children not left behind was statistically significant, which may be related to the lack of care and emotional support from parents (41).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study examined the association of many factors with NSSI, found that students attending vocational high schools had a significantly higher prevalence of NSSI than middle school students as well as general high schools, and that school category was also an independent risk factor for NSSI in the regression equation, which may be due to the lower self-efficacy and lower self-esteem of vocational high school students compared to their counterparts in general middle and high schools (40). The prevalence of NSSI by gender was statistically significant and also an independent risk factor for NSSI, which is also consistent with most previous studies (19)(20)(21)(22). The difference in NSSI detection rates between those left-behind children and those children not left behind was statistically significant, which may be related to the lack of care and emotional support from parents (41).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, numerous studies have shown that self-injurious behaviors show significant differences by gender (19)(20)(21)(22). There may be differences in the psychological mechanisms underlying the occurrence of non-suicidal self-injurious behaviors across genders (23-25).…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence of self-harm in female adolescents is in line with the results of a number of studies [7,8,16]. Most of them explain these outcomes with the statement that women regulate their emotions in different ways to men [17,18].…”
Section: Discussionsupporting
confidence: 77%
“…A statistically significantly higher prevalence of self-harm in men was recorded in Germany [5], and also in adolescents in China [6]. On the contrary, other studies report a preponderance of women among self-harming individuals [7,8], or have stated that they have found no difference between the genders related to prevalence [9,10].…”
Section: Introductionmentioning
confidence: 87%
“…Female adolescents have been reported to be more sensitive to parental socio-economic status than males [ 34 ]. It is well-known that female adolescence is associated with high stress levels due to significant changes regarding physical, psychological, and social aspects [ 35 ]. Moreover, female adolescents from poor families are more likely to join the labor market at an early age and to forgo college admission than male adolescents in Korea according to a National Youth Policy report [ 34 ].…”
Section: Discussionmentioning
confidence: 99%